Minority salience and political extremism - Tommaso Colussi; Ingo Eduard Isphording; Nico Pestel (Università Cattolica del Sacro Cuore, Dipartimento di Economia e Finanza (DISCE), 2019)
We investigate how changes in the salience of a minority group affect the majority group's voting behavior. Specifically, we focus on Muslim communities and their increased salience in daily life during Ramadan. To estimate a causal effect, we exploit exogenous variation in the distance of German federal and state elections to the month of Ramadan over the 1980-2013 period. Our findings reveal an increased polarization of the electorate: vote shares for both right- and left-wing extremist parties increasein municipalities where mosques are located when the election date is closer to Ramadan. We use individual-level survey data to provide evidence on potential mechanisms. During Ramadan respondents perceive the share of foreign-born people living in their country as larger and reveal more negative attitudes towards Muslims. We complement these findings with evidence on increased numbers of violent attacks against Muslim communities shortly after Ramadan.
Keywords: D72; D74; J15; D91; 330; Salience; Muslims; Behavioral Political Economy; Right-Wing Extremism